Relation between the maximum modulus and the maximal term of Dirichlet series in terms of a convergence class - Mulyava, Oksana; Sheremeta, Miroslav; Sumyk, O. (My University, 2012)
A relation between the growth of maximum modulus and the growth maximal term of Dirichlet series in terms of a convergence class is investigated. Досліджено зв’язок між зростанням максимуму модуля і зростанням максимального члена ряду Діріхле в термінах класів збіжності.
Keywords: Dirichlet series; convergence class; ряди Діріхле; клас збіжності; кафедра вищої математики імені проф. Можара В. І.